DOING YOUR HOMEWORK: THE USE OF SOCIAL MEDIA AS A FRIENDSHIP FILTER - Standlee, Alecea Irene (AoIR Selected Papers of Internet Research, 2018)
This article explores the emergence of technologically integrated relationship practices among college students in two U.S. universities. This work is situated within the significant body of social research and popular cultural discourse surrounding the consequences of technology and cultural integration among young adults. Analyzing interviews with 52 participants, I explore how they construct, establish and maintain cultural practices and social norms that shape peer interaction, social networks and interpersonal relationships in offline and online settings. This paper focuses specifically on the emergence of techno-social cultural norms that impact friendship and social network construction. Findings suggest the establishment and maintenance of friendships using social networks frequently includes the use of social media profiles as means to collect social and political attitude data on potential friends. Some participants report the use of such data as essential to the decision-making process utilized while establishing and maintaining offline friendships. Motivations for this practice include safety and security, social normativity and a desire for efficiency. Furthermore, participants articulate a social and politically homogeneous friendship network as a desirable outcome to data collection. These findings contribute to our ongoing understanding of the role of informational echo chambers within a technologically integrated social environment.